Effects of Radon From Hot Springs on Lymphocyte Subsets in Peripheral Blood - Chunnan Piao; Mei Tian; Hongjun Gao; Yanxiao Gao; Jianlei Ruan; Lina Wu; Gang Gao; Lirong Yi; Jianxiang Liu (SAGE Publishing, 2020)
Objective: To analyze changes in immune functions by detecting lymphocyte subsets in the peripheral blood of residents in the vicinity of radon from hot springs. Methods: Two groups were randomly selected; 61 residents in the vicinity of the hot springs were assigned to the radon group, and 51 residents with a similar lifestyle and habits but no contact with hot springs were assigned to the control group. The percentages of lymphocyte subsets (CD3 + , CD4 + CD8 − , CD4 − CD8 + , CD4 + /CD8 + , and TCR/CD3) in the 2 groups were evaluated on a FACS Aria flow cytometer. The absolute values of lymphocytes (LYMPH#) and percentages of lymphocytes (LYMPH%) were measured by an automatic blood analyzer. Results: In the radon group, the numbers of CD3 + ( Z = −0.140, P > .05) and CD4 + CD8 − ( Z = −0.964, P > .05) T cells were higher, as compared with the controls, but this difference was not significant. In addition, the number of CD4 − CD8 + ( t = −2.141, P < .05) T cells was significantly lower in the radon group. Furthermore, the average ratios of CD4 + /CD8 + ( t = −2.201, P < .05) and TCR/CD3 ( t = 2.047, P < .05) cells were significantly higher in the radon group than in the controls. Compared with the control group, the LYMPH# ( t = −0.485, P > .05) and LYMPH% (Z = −0.835, P > .05) showed no significant change. Conclusion: Radon-rich hot springs could alter the proportions of lymphocyte subsets and possibly affect immunologic functions.